Artificial intelligence technologies in media and culture: Legal regulation - Ivashchenko, Victoria; Ivashchenko, Daria; Honcharova, Yuliia; Dyachenko, Roksolana; Koreniuk, Olha (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2024)
The study aims to fill the literature's gaps concerning the legal consequences of artificial intelligence use. The study combines experimental modelling of the interaction of artificial intelligence with media content and cultural artefacts. Machine learning methods were used, particularly natural language processing and deep learning. A comparative-legal analysis of the regulatory framework with LexisNexis and Westlaw resources was conducted. Qualitative methods, such as regression and analysis of variance, evaluated correlations between the influence of artificial intelligence and content changes. The findings showed significant differences in the effect of artificial intelligence on media platforms and cultural institutions. Artificial intelligence has a larger influence on content recommendations and user engagement in media rather than in culture. Tukey's Honestly Significant Difference test confirmed the statistical significance of these results, indicating the need for adapted regulatory approaches. Artificial intelligence technologies can improve media content and cultural participation, but current regulations do not address new challenges. The findings underline the necessity of developing special regulatory norms for ethical artificial intelligence use, particularly within aspects of intellectual property and digital rights management.